Green Tape: Stakeholders’ Positive Perceptions Of The Administrative Rules Governing Public Participation In The Hampton Roads Transportation Planning Organization - Kadir, Nadhrah A (Universiti Sains Malaysia, 2016)

(untitled)
This paper explores multiple stakeholders’ perceptions with regard to administrative rules governing public participation in the Hampton Roads Transportation Planning Organization (HRTPO) in Virginia. In 2007, the HRTPO received conditional certification during its quadrennial review with seven corrective actions related to public participation. Subsequently, it started to reform its public participation practices, and in 2012 it received full certification. This study explores how the HRTPO stakeholders perceive the administrative rules that govern public participation processes, more positively or more negatively. Before 2007, top management officials had pessimistic perceptions of public participation in general and the rules in particular. The negative perceptions changed when new senior staff arrived in 2008 and initiated many reforms. This study draws on interview data collected from 16 stakeholders involved in public participation processes in the HRTPO such as officials from the Federal Highway Administration (FHWA), staff of the HRTPO, and citizens who sit on the Citizen Transportation Advisory Committee (CTAC). Using these data coupled with relevant archival documents and guided by DeHart-Davis’s green tape attributes (2009), this study found that stakeholders perceived the rules more positively than they did in 2007.